A new nonlinearly tapered FGM piezoelectric energy harvester. (15th October 2018) - Keshmiri, Alireza; Wu, Nan; Wang, Quan
Highlights: FGM piezoelectric energy harvester with general geometry is modelled analytically. Adomian decomposition method and a modified mathematical procedure are used. Dynamic response under base motion is derived to harvest vibrational energy. Effects of geometry, FGM and excitation frequency are comprehensively studied. The non-uniform FGM design can significantly increase the electrical output. Abstract: This work presents an analytical model for the development of a piezoelectric energy harvester with general nonlinear geometry and functionally graded material (FGM) properties based on Adomian decomposition method. The model is applied to geometrically and materially non-uniform beams with structural strain rate damping and surface bonded piezoelectric layers to derive the dynamic response of the smart structure to base motion excitations and efficiently harvesting the subsequent vibrational energy. Firstly, the steady state vibration response of the smart non-uniform FGM beam subjected to a harmonic base motion is obtained and then electromechanical outputs of the piezoelectric patches are analytically derived. Furthermore, a comprehensive parametric study for bimorph piezoelectric energy harvesters with different nonlinearly tapered geometry and FGM properties in a wide frequency range has been done. Considering the same volume of the harvester, it is demonstrated that the novel non-uniform FGM design can significantly increase the electrical output of the harvester by more than 19.76 times compared to the traditional uniform homogenous design. With the presented methodology, optimum structural design for piezoelectric energy harvesters with respect to the operation frequency domain can be effectively achieved.